2016
DOI: 10.1097/ico.0000000000000989
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Alterations in Corneal Nerves, Dendritic Cells, and Tear Cytokine Levels in Ocular Surface Disease

Abstract: This review summarizes recent literature regarding corneal imaging in human subjects using in vivo confocal microscopy and corneal immune cells, nerves, and tear cytokine levels in ocular surface diseases as well as corneal immune privilege. The significance of interactions between corneal immune cells and nerves in health, neurotrophic keratopathy, and infectious keratitis are discussed. Furthermore, bilateral alterations of immune cells and nerves in clinically unilateral corneal diseases and the link to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 90 publications
1
39
1
3
Order By: Relevance
“…The mechanisms underlying these contralateral changes are unclear, especially given that there are other examples of unilateral corneal injury and disease states that affect both contralateral nerve density and sensation [21]. Possible mechanisms of bilateral changes induced by unilateral corneal injury include bilateral increases in dendritic cells which mediate immune responses and alterations in tear cytokines in the context of unilateral bacterial keratitis [56]. Others have suggested that contralateral hyperalgesia, or mirror pain, after nerve injury may be related to changes in the peripheral nervous system, central pathways and/or the activation of immunocompetent cells such as cytokines, macrophages, microglia and astrocytes [15; 49].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying these contralateral changes are unclear, especially given that there are other examples of unilateral corneal injury and disease states that affect both contralateral nerve density and sensation [21]. Possible mechanisms of bilateral changes induced by unilateral corneal injury include bilateral increases in dendritic cells which mediate immune responses and alterations in tear cytokines in the context of unilateral bacterial keratitis [56]. Others have suggested that contralateral hyperalgesia, or mirror pain, after nerve injury may be related to changes in the peripheral nervous system, central pathways and/or the activation of immunocompetent cells such as cytokines, macrophages, microglia and astrocytes [15; 49].…”
Section: Discussionmentioning
confidence: 99%
“…22 Moreover, the corneal endothelial cells were damaged with an altered central corneal thickness in patients with uveitis, [14][15][16]23 whereas inflammatory cell infiltration into the corneal stoma was also observed during the onset of anterior uveitis. 24 On the other hand, the same inflammatory mediators and immune cells increased with uveitis and keratopathies, 17,25,26 indicating that a general immune reaction and inflammatory response could cause both uveitis and several types of keratopathies. In clinical studies, systemic disorders featuring immune and inflammation impairment, such as rheumatoid arthritis and psoriasis, were associated with the occurrence of uveitis and keratopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Integrity of the corneal sub‐basal nerve plexus is regulated by interactions between immune cells and nerve fiber endings . Their communication is crucial controlling the corneal immune status . A disruption of these fine‐tuned neuro‐immune interactions may alter corneal innervation.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Their communication is crucial controlling the corneal immune status. 23,24 A disruption of these fine-tuned neuro-immune interactions may alter corneal innervation. Hence, they are promising targets for pathophysiological mechanisms in small fiber pathology.…”
mentioning
confidence: 99%